2008
DOI: 10.1097/yic.0b013e32830cebed
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and tolerability of fixed-dose desvenlafaxine 50 and 100 mg/day for major depressive disorder in a placebo-controlled trial

Abstract: The objective of this study was to assess the efficacy, safety, and tolerability of desvenlafaxine (administered as desvenlafaxine succinate) 50 and 100 mg/day for major depressive disorder (MDD). A multicenter, randomized, double-blind, placebo-controlled trial was conducted in Europe and South Africa. Outpatients with MDD received fixed-dose desvenlafaxine (50 or 100 mg/day) or placebo for 8 weeks. The primary efficacy variable was the 17-item Hamilton Rating Scale for Depression total score; secondary measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 21 publications
3
101
2
1
Order By: Relevance
“…Studies investigating desvenlafaxine at lower doses (ie, 50 and 100 mg/d) have demonstrated better tolerability and lower occurrences of AEs [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating desvenlafaxine at lower doses (ie, 50 and 100 mg/d) have demonstrated better tolerability and lower occurrences of AEs [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of desvenlafaxine administration in healthy adults [13] and in patients with MDD [14,15] have also demonstrated sustainedrelease characteristics that support once-daily administration. For clinical use, it is important to determine if the type of food intake affects pharmacokinetic behavior, as variability could result in unpredictable clinical effects and might necessitate specific dosing guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36] Several published abstracts were also reviewed: including a fl exible dose trial of DVS 200 to 400 mg, 37 a trial comparing DVS 50 and 100 mg to placebo with a duloxetine reference arm, 8 as well as two unpublished pooled analyses, the fi rst involving 7 short-term trials with DVS doses between 100 and 400 mg 39 and the second from 2 trials with DVS at 50 and 100 mg. 40 Other studies of DVS as a treatment for vasomotor symptoms of menopause and pain were not reviewed. No published trials for generalized anxiety disorder or other anxiety disorders were located.…”
Section: Effi Cacy In Clinical Trialsmentioning
confidence: 99%
“…However, in the placebo-controlled trial with desvenlafaxine, the latest antidepressant approved by FDA (Young & Plosker, 2008), the mean drug-placebo improvement score on HAMD was assumed to be 3.0 and the pooled standard deviation 8.0, resulting in an expected effect size of 0.38 (Boyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%